Effectiveness of Generation of Red Ginger and Mint Leaves to Reduce Hyperemisis Gravidarum in the 1st Trimester Pregnant Women - Eka Rahayuningsih; Tuty Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The incidence of emesis gravidarum is 14 % of all expectant women worldwide. In five European, American, and Australian jurisdictions, approximately 73.5 percent of pregnant women experience emesis. Up to 75 % of expectant women in Indonesia experience nausea and vomiting in the first trimester or early pregnancy. Several pharmacological and non-pharmacological actions can contribute to efforts to reduce the frequency of regurgitation. Non-pharmacologically, herbal plants, such as red ginger and peppermint leaves, are readily available. Methods : One-group, quasi-experimental, pretest-posttest design. This study's sample consisted of all 35 expectant women in the first trimester of PMB "E" from June to December 2022, and the sampling technique employed was a complete sample. Results : The average intensity of nausea and vomiting in first-trimester expectant women was 9.54 prior to consuming red ginger and mint leaves, and 5.46 afterward. Red ginger water and mint leaves are efficacious in reducing hyperemia gravidarum in first-trimester pregnant women (p-value = 0.000). Conclusions: Red ginger water and mint leaves are effective in reducing hyperemisis gravidarum in first-trimester expectant women. It is anticipated that the midwife will provide pregnant women with guidance on how to prepare a decoction of ginger and mint leaves to alleviate hyperemesis gravidarum.